Aplicación móvil para el cálculo volumétrico en plantaciones de teca (Tectona grandis L. f.) - Gamboa Vega , José Deiver (2024)
This research project focuses on the development of a mobile application to improve the accuracy and efficiency in the calculation of the volume of teak plantations (Tectona grandis L. f.) at the La María campus of the Quevedo State Technical University. The initiative arises from the difficulty in obtaining accurate measurements using conventional methods, which can lead to inefficient forest management and overexploitation of resources. Through a mixed methodological approach that combines experimental and applied research with advanced technologies such as TensorFlow Lite and Firebase, the aim is to develop a tool that facilitates data collection and analysis in the field. The application, created in Android Studio and programmed in Java, employs deep learning models to estimate the volume of wood, offering a friendly and functional interface for users. The validation of the tool was carried out through experimental tests at the university, evidencing a substantial improvement in the accuracy of the measurements compared to traditional techniques. This project not only presents a technological solution to the challenge of measurement in teak plantations, but also aligns with global efforts towards sustainable forest management, highlighting the importance of integrating new technologies in the forestry sector.